Risk-oriented approach to identifying hazards in the construction industry of Ukraine (Academic journal Industrial Machine Building Civil Engineering, 2021)
An attempt to improve the analytical method for determining the criteria for the risk degree in the construction industry was presented in this paper. The risk management process as a set of actions that is part of the overall business management was analyzed. Features of systemic occupational safety risk management were identified. The stages of an occupational safety management system design based on hazard identification were presented. The main objectives of the risk-oriented approach to ensuring the systems’ reliability based on the acceptable risk concept were formulated. A method for determining the criteria by which the risk degree of an accident or an injury is assessed, for the possibility of planning supervisory activities at the enterprise was proposed.
Keywords: construction; injuries; risk degree; risk criteria; risk-oriented approach